Method for producing particles of crosslinked polymer containing alicyclic structure

JP7631984B2Active Publication Date: 2025-02-19ZEON CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021056231
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-29
Publication Date
2025-02-19
Estimated Expiration
2041-03-29

AI Technical Summary

Benefits of technology

【0011】 本発明によれば、粒子径が小さく、円形度の高い脂環式構造含有架橋重合体の粒子を製造するための方法、および、このような製造方法を用いて得られた脂環式構造含有架橋重合体の粒子を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007631984000001
    Figure 0007631984000001
  • Figure 0007631984000002
    Figure 0007631984000002
Patent Text Reader

Abstract

To provide a method for producing particles of a cross-linked polymer containing an alicyclic structure which have a small particle diameter and high circularity.SOLUTION: There is provided a method for producing particles of a cross-linked polymer containing an alicyclic structure which comprises: a dissolution step of dissolving a polymer containing an alicyclic structure in an organic solvent to obtain a solution (a); a radical generator addition step of adding a radical generator to (a) to obtain a solution (b); an emulsification step of mixing an aqueous medium containing a dispersant and the solution (b) and emulsifying the mixture to obtain an emulsion (c); a cross-linking step of heating the emulsion (c) at a heating temperature T1 [°C] to obtain a slurry containing particles of a cross-linked polymer containing the alicyclic structure; an organic solvent removal step of heating the emulsion (c) or the slurry at a heating temperature T2 [°C] to remove the organic solvent; and a recovery step of recovering particles of the cross-linked polymer containing the alicyclic structure, wherein the heating temperature T1 is a temperature higher than the 10-hour half-life temperature of the radical generator and the temperature T2 in the organic solvent removal step is 40 to 95°C.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing particles of an alicyclic structure-containing crosslinked polymer. [Background technology]

[0002] Polymer particles made of various polymers are used as light diffusing agents, powder coating materials, toner materials, inks, spacers for liquid crystal displays and the like, fillers, antiblocking agents, lubricant components, powders for forming three-dimensional objects, and the like.

[0003] As such polymer particles, alicyclic structure-containing polymer particles such as cyclic olefin resins have been attracting attention from the viewpoint that they are suitable for optical applications due to their high glass transition temperature and light transmittance, and small anisotropy of refractive index.For example, Patent Document 1 proposes a method for producing cyclic olefin resin particles, which includes step 1 of dissolving a cyclic olefin resin in an organic solvent, step 2 of emulsifying the solution a obtained in step 1 in an aqueous solution b containing 0 to 20 mass % of a surfactant, and step 3 of recovering and drying the cyclic olefin resin particles dispersed in the emulsion obtained in step 2.

[0004] On the other hand, in recent years, polymer particles are required to have a high circularity in order to meet high required properties in various applications, but the cyclic olefin resin particles obtained by the method described in Patent Document 1 have a low circularity and cannot meet such requirements. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2010-59360 A Summary of the Invention [Problem to be solved by the invention]

[0006] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a method for producing particles of an alicyclic structure-containing crosslinked polymer having a small particle size and a high degree of circularity. [Means for solving the problem]

[0007] The present inventors have conducted studies to achieve the above object, and have found that it is possible to produce particles of an alicyclic structure-containing crosslinked polymer having a small particle size and a high degree of circularity by dissolving an alicyclic structure-containing polymer in an organic solvent, then adding a radical generator to the resulting solution, emulsifying the solution in an aqueous medium containing a dispersant, and crosslinking the alicyclic structure-containing polymer in the emulsion state at a specific heating temperature, thereby completing the present invention.

[0008] That is, according to the present invention, the method includes a dissolving step of dissolving an alicyclic structure-containing polymer in an organic solvent for dissolution to obtain a solution (a); a radical generator addition step of obtaining a solution (b) by adding a radical generator to the solution (a) obtained in the dissolving step; an emulsification step of mixing an aqueous medium containing a dispersant with the solution (b) and emulsifying the mixture to obtain an emulsion (c); The emulsion (c) is heated to a temperature T 1 a crosslinking step of crosslinking the alicyclic structure-containing polymer in the aqueous medium by heating at a temperature of [° C.] to obtain a slurry containing particles of the alicyclic structure-containing crosslinked polymer; Before or after the crosslinking step, the emulsion (c) or the slurry is heated to a heating temperature T 2 an organic solvent removal step of removing the organic solvent in the emulsion (c) or the slurry by heating at [° C.]; A recovery step of recovering particles of the alicyclic structure-containing crosslinked polymer from the slurry, The heating temperature T 1 is a temperature equal to or higher than the 10-hour half-life temperature of the radical generator, and the heating temperature T 2The present invention provides a method for producing particles of an alicyclic structure-containing crosslinked polymer, in which the temperature is 40 to 95°C.

[0009] In the method for producing particles of an alicyclic structure-containing crosslinked polymer of the present invention, it is preferable that the emulsion (c) further contains an organic solvent for addition different from the organic solvent for dissolution used in the dissolving step. In the method for producing particles of an alicyclic structure-containing crosslinked polymer of the present invention, the absolute value of the difference between the SP value of the organic solvent for dissolution and the SP value of the organic solvent for addition is 0.2 to 14 MPa. 1 / 2 It is preferable that:

[0010] Furthermore, according to the present invention, there is provided particles of an alicyclic structure-containing crosslinked polymer having a volume average particle size of 0.5 to 100 μm and an average circularity of 0.90 to 1.00. The particles of the alicyclic structure-containing crosslinked polymer of the present invention preferably satisfy the following formula (1) when the loss tangent (tan δ) at 200°C is defined as "tan δ(200)" and the loss tangent (tan δ) at 250°C is defined as "tan δ(250)" in a temperature dependency curve of the loss tangent (tan δ) obtained by performing dynamic viscoelasticity measurement at a frequency of 1 Hz. {tanδ(200)-tanδ(250)} / 50>0 (1) Effect of the Invention

[0011] According to the present invention, there can be provided a method for producing particles of an alicyclic structure-containing crosslinked polymer having a small particle size and a high degree of circularity, and particles of an alicyclic structure-containing crosslinked polymer obtained by such a production method. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] <Method for producing particles of alicyclic structure-containing crosslinked polymer> The method for producing particles of an alicyclic structure-containing crosslinked polymer of the present invention includes the steps of: A dissolving step of dissolving the alicyclic structure-containing polymer in an organic solvent for dissolution to obtain a solution (a); a radical generator addition step of obtaining a solution (b) by adding a radical generator to the solution (a) obtained in the dissolving step; an emulsification step of mixing an aqueous medium containing a dispersant with the solution (b) and emulsifying the mixture to obtain an emulsion (c); The emulsion (c) is heated to a temperature T 1 a crosslinking step of crosslinking the alicyclic structure-containing polymer in the aqueous medium by heating at a temperature of [° C.] to obtain a slurry containing particles of the alicyclic structure-containing crosslinked polymer; Before or after the crosslinking step, the emulsion (c) or the slurry is heated to a heating temperature T 2 an organic solvent removal step of removing the organic solvent in the emulsion (c) or the slurry by heating at [° C.]; A recovery step of recovering particles of the alicyclic structure-containing crosslinked polymer from the slurry, The heating temperature T 1 is a temperature equal to or higher than the 10-hour half-life temperature of the radical generator, and the heating temperature T 2 is 40 to 95°C.

[0013] <Dissolution process> The dissolving step in the production method of the present invention is a step of obtaining a solution (a) by dissolving the alicyclic structure-containing polymer in an organic solvent for dissolution.

[0014] The alicyclic structure-containing polymer is a polymer having an alicyclic structure in its structural unit, and may be either a polymer having an alicyclic structure in its main chain or a polymer having an alicyclic structure in its side chain. From the viewpoint of excellent mechanical strength and heat resistance, however, a polymer containing an alicyclic structure in its main chain is preferred.

[0015] Examples of the alicyclic structure include saturated alicyclic hydrocarbon (cycloalkane) structures, unsaturated alicyclic hydrocarbon (cycloalkene, cycloalkyne) structures, etc. Among these, from the viewpoint of excellent mechanical strength and heat resistance, cycloalkane structures and cycloalkene structures are preferred, and among these, cycloalkane structures are particularly preferred.

[0016] The number of carbon atoms constituting the alicyclic structure is preferably 4 or more, more preferably 5 or more, and preferably 30 or less, more preferably 20 or less, particularly preferably 15 or less, per one alicyclic structure.

[0017] Examples of the polymer containing an alicyclic structure include norbornene-based polymers, monocyclic olefin polymers, cyclic conjugated diene polymers, vinyl alicyclic hydrocarbon polymers, and hydrogenated products thereof. Among these, norbornene-based polymers are preferred because of their excellent heat resistance and low moisture absorption.

[0018] The norbornene-based polymer is preferably a polymer containing 20 mol % or more of structural units derived from norbornenes, or a hydrogenated product thereof, and the norbornene-based polymer may also contain structural units derived from compounds other than norbornenes.

[0019] Although the norbornenes capable of forming a structural unit derived from norbornenes are not particularly limited, it is preferable to use at least norbornenes exhibiting crosslinking properties, since the crosslinking reaction can be suitably carried out in the crosslinking step described later. Although the norbornenes exhibiting crosslinking properties are not particularly limited, norbornenes having a carbon-carbon double bond in a portion other than the norbornene structure (for example, norbornenes having a vinyl group, an alkylidene group, an acryloyl group, or a methacryloyl group) and norbornenes having a tertiary carbon in a portion other than the norbornene structure can be mentioned. The norbornenes exhibiting crosslinking properties may be used alone or in combination of two or more.

[0020] Specific examples of norbornenes having a carbon-carbon double bond in a portion other than the norbornene structure include bicyclic norbornenes having a methacryloyl group, such as 5-methacryloxy-2-norbornene, 5-methacryloxymethyl-2-norbornene, 5-(2-methacryloxyethyl)-2-norbornene, 5-(3-methacryloxypropyl)-2-norbornene, 5-(4-methacryloxybutyl)-2-norbornene, and 5-(5-methacryloxypentyl)-2-norbornene; Bicyclic norbornenes having an acryloyl group, such as 5-acryloxy-2-norbornene, 5-acryloxymethyl-2-norbornene, 5-(2-acryloxyethyl)-2-norbornene, 5-(3-acryloxypropyl)-2-norbornene, 5-(4-acryloxybutyl)-2-norbornene, and 5-(5-acryloxypentyl)-2-norbornene; Bicyclic norbornenes having an alkylidene group, such as 5-methylidene-2-norbornene, 5-ethylidene-2-norbornene, 5-n-propylidene-2-norbornene, 5-isopropylidene-2-norbornene, and 5,6-diethylidene-2-norbornene; 3-ring norbornenes such as dicyclopentadiene; 9-Methylidenetetracyclo[6.2.1.1 3,6 .0 2,7 ]dodec-4-ene, 9-methylidene-10-methyltetracyclo[6.2.1.1 3,6 .0 2,7 ]dodec-4-ene, 9-methylidene-10-ethyltetracyclo[6.2.1.1 3,6 .0 2,7 ]dodec-4-ene, 9-methylidene-10-isopropyltetracyclo[6.2.1.1 3,6 .0 2,7 ]dodec-4-ene, 9-methylidene-10-butyltetracyclo[6.2.1.1 3,6 .0 2,7 ]dodec-4-ene, 9-ethylidenetetracyclo[6.2.1.1 3,6 .0 2,7]dodec-4-ene (ethylidenetetracyclododecene), 9-ethylidene-10-methyltetracyclo[6.2.1.1 3,6 .0 2,7 ]dodec-4-ene, 9-ethylidene-10-ethyltetracyclo[6.2.1.1 3,6 .0 2,7 ]dodec-4-ene, 9-ethylidene-10-isopropyltetracyclo[6.2.1.1 3,6 .0 2,7 ]dodec-4-ene, 9-ethylidene-10-butyltetracyclo[6.2.1.1 3,6 .0 2,7 ]dodec-4-ene, 9-n-propylidenetetracyclo[6.2.1.1 3,6 .0 2,7 ]dodec-4-ene, 9-n-propylidene-10-methyltetracyclo[6.2.1.1 3,6 .0 2,7 ]dodec-4-ene, 9-n-propylidene-10-ethyltetracyclo[6.2.1.1 3,6 .0 2,7 ]dodec-4-ene, 9-n-propylidene-10-isopropyltetracyclo[6.2.1.1 3,6 .0 2,7 ]dodec-4-ene, 9-n-propylidene-10-butyltetracyclo[6.2.1.1 3,6 .0 2,7 ]dodec-4-ene, 9-isopropylidenetetracyclo[6.2.1.1 3,6 .0 2,7 ]dodec-4-ene, 9-isopropylidene-10-methyltetracyclo[6.2.1.1 3,6 .0 2,7 ]dodec-4-ene, 9-isopropylidene-10-ethyltetracyclo[6.2.1.1 3,6 .0 2,7 ]dodec-4-ene, 9-isopropylidene-10-isopropyltetracyclo[6.2.1.1 3,6 .0 2,7 ]dodec-4-ene, 9-isopropylidene-10-butyltetracyclo[6.2.1.1 3,6 .0 2,7 ]dodec-4-ene, 9-vinyltetracyclo[6.2.1.13,6 .0 2,7 ]dodec-4-ene, 9-propenyltetracyclo[6.2.1.1 3,6 .0 2,7 ]Dodec-4-ene and other 4-ring norbornenes having an alkylidene group; etc.

[0021] Furthermore, examples of norbornenes having a tertiary carbon at a position other than the norbornene structure include norbornenes having structures such as those shown in the following general formulas (1) to (4), which have a tertiary carbon at a position other than the norbornene structure. [ka] In the formula, R 1 ~R 4 may be the same or different and are selected from the group consisting of a hydrogen atom, a halogen atom, and an organic group; R 1 ~R 4 At least one of R is not a hydrogen atom. 1 and R 2 , R 3 and R 4 may combine together to form a divalent hydrocarbon group, R 1 or R 2 And, R 3 or R 4 may form a ring together. In addition, n represents an integer of 1 to 2. 1 ~R 4 Examples of the alkyl group include chain hydrocarbon groups such as alkyl groups and alkenyl groups, carbonyl groups, and nitrile groups.

[0022] In addition, as the norbornenes capable of forming a structural unit derived from norbornenes, norbornenes other than the above-mentioned crosslinkable norbornenes can be used. For example, bicyclic norbornenes such as norbornene, 5-methyl-2-norbornene, 5-ethyl-2-norbornene, 5-propyl-2-norbornene, 5-phenyl-2-norbornene, 5,6-dimethyl-2-norbornene, and 5,5,6-trimethyl-2-norbornene; tricyclic norbornenes such as 1,2-dihydrodicyclopentadiene; tetracyclo[6.2.1.1 3,6 .0 2,7 ]dodec-4-ene (tetracyclododecene, TCD), 9-methyltetracyclo[6.2.1.1 3,6 .0 2,7 ]dodec-4-ene, 9-ethyltetracyclo[6.2.1.1 3,6 .0 2,7 ]dodec-4-ene, 9,10-dimethyltetracyclo[6.2.1.1 3,6 .0 2,7 ]Dodec-4-ene, 1,4-methano-1,4,4a,9a-tetrahydrofluorene (MTF), and other 4-ring norbornenes; tricyclopentadiene, and other 5-ring norbornenes; and the like. The norbornenes other than the crosslinkable norbornenes may be used alone or in combination of two or more kinds.

[0023] The norbornene-based polymer may be any polymer containing 20 mol % or more of a structural unit derived from a norbornene, or a hydrogenated product thereof, such as an addition polymer containing a structural unit derived from a norbornene, or a hydrogenated product thereof (hereinafter referred to as a "norbornene-based addition polymer"), or a ring-opening polymer containing a structural unit derived from a norbornene, or a hydrogenated product thereof (hereinafter referred to as a "norbornene-based ring-opening polymer"); from the viewpoint of superior moldability, heat resistance, low moisture absorption, dimensional stability, and light weight, a hydrogenated ring-opening polymer containing a structural unit derived from a norbornene is preferred.

[0024] Examples of the norbornene-based addition polymer include addition polymers of norbornenes, addition polymers of norbornenes and other compounds capable of addition copolymerization with norbornenes, and hydrogenated products thereof.

[0025] The norbornenes that can be used in the preparation of the norbornene-based addition polymer are not particularly limited, and the above-mentioned norbornenes can be used. These norbornenes may be used alone or in combination of two or more. As the norbornenes, it is preferable to use ones that contain at least norbornenes exhibiting crosslinking properties, and it is more preferable to use ones that contain at least norbornenes having an alkylidene group, and 9-ethylidenetetracyclo[6.2.1.1 3,6 .0 2,7 It is more preferable to use one containing at least ]dodec-4-ene (ethylidenetetracyclododecene).

[0026] Other compounds that can be used in the preparation of norbornene-based addition polymers are not particularly limited as long as they are compounds capable of addition copolymerization with norbornenes, and examples thereof include α-olefins having 2 to 20 carbon atoms, such as ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 3-methyl-1-butene, 3-methyl-1-pentene, 3-ethyl-1-pentene, 4-methyl-1-pentene, 4-methyl-1-hexene, 4,4-dimethyl-1-hexene, 4,4-dimethyl-1-pentene, 4-ethyl-1-hexene, 3-ethyl-1-hexene, 1-octene, and 1-decene; cyclobutene, cyclopentene, cyclohexene, cycloheptene, cyclooctene, cyclodecene, cyclododecene, and tricyclo[6.2.1.0] 2,7] undec-4-ene (tricycloundecene) and cycloolefins other than norbornenes such as derivatives thereof; α,β-ethylenically unsaturated nitrile compounds such as acrylonitrile and methacrylonitrile; α,β-ethylenically unsaturated carboxylic acid compounds and ester compounds thereof such as acrylic acid, methacrylic acid, acrylic acid esters, and methacrylic acid esters; etc. Among these, from the viewpoint of the ease of polymerization of norbornene-based addition polymers, α-olefins having 2 to 20 carbon atoms are preferred, and ethylene is more preferred.

[0027] The content of structural units derived from norbornenes in the norbornene-based addition polymer is 20 mol % or more, preferably 50 mol % or more, and more preferably 80 mol % or more, and it is particularly preferred that the polymer essentially consists of structural units derived from norbornenes (i.e., the content of structural units derived from norbornenes is 100 mol %).

[0028] The method for preparing the norbornene-based addition polymer is not particularly limited, and the norbornene-based addition polymer can be obtained by addition polymerization of a monomer composition containing the above-mentioned norbornenes and optionally other compounds, and further hydrogenation as necessary. Note that both the addition polymerization and hydrogenation can be carried out using known methods. For example, the addition polymerization can be carried out using the method described in JP-A-2008-144013.

[0029] Examples of norbornene-based ring-opening polymers include ring-opening polymers of norbornenes, ring-opening polymers of norbornenes and other compounds capable of ring-opening copolymerization with norbornenes, and hydrogenated products thereof.

[0030] The norbornenes that can be used in the preparation of the norbornene-based ring-opening polymer are not particularly limited, and the above-mentioned norbornenes can be used. These norbornenes may be used alone or in combination of two or more. As the norbornenes, it is preferable to use one that contains at least a norbornene exhibiting crosslinking properties, and it is more preferable to use one that contains at least a norbornene having an alkylidene group, and 9-ethylidenetetracyclo[6.2.1.1 3,6 .0 2,7 It is more preferable to use one containing at least ]dodec-4-ene (ethylidenetetracyclododecene).

[0031] The other compounds that can be used in the preparation of norbornene-based ring-opening polymers are not particularly limited as long as they are compounds capable of ring-opening copolymerization with norbornenes, and for example, the same compounds as those that can be used in the preparation of the above-mentioned norbornene-based addition polymers can be used.

[0032] The method for preparing the norbornene-based ring-opening polymer is not particularly limited, and the norbornene-based ring-opening polymer can be obtained by ring-opening polymerization of a monomer composition containing the above-mentioned norbornenes and optionally other compounds, and optionally hydrogenation. The ring-opening polymerization and hydrogenation can both be carried out using known methods. For example, the ring-opening polymerization and hydrogenation can be carried out using the method described in JP 2017-179001 A.

[0033] The organic solvent for dissolution used in the dissolution step is not particularly limited as long as it can dissolve the alicyclic structure-containing polymer, but examples thereof include hydrocarbons such as petroleum ether, pentane, hexane, heptane, octane, nonane, and decane; cyclic hydrocarbons such as cyclopentane, cyclohexane, methylcyclohexane, cycloheptane, cyclooctane, decalin, and norbornane; aromatic hydrocarbons such as benzene, toluene, xylene, ethylbenzene, cumene, and chlorobenzene; halogenated hydrocarbons such as dichloromethane, dichloroethane, chlorobutane, chloroform, and tetrachloroethylene; esters such as methyl acetate, ethyl acetate, n-butyl acetate, isobutyl acetate, and methyl propionate; ethers such as dibutyl ether, tetrahydrofuran, dimethoxyethane, and dioxane; and amides such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone. These may be used alone or in combination of two or more. Among these, from the viewpoint of excellent solubility of the alicyclic structure-containing polymer, cyclic hydrocarbons are preferred, and cyclohexane is more preferred.

[0034] The amount of the organic solvent used in the dissolution step is not particularly limited, but is preferably 300 to 2000 parts by weight, more preferably 400 to 1000 parts by weight, relative to 100 parts by weight of the alicyclic structure-containing polymer. The amount of the organic solvent used in the dissolution step is preferably an amount such that the content of the alicyclic structure-containing polymer in the solution (a) obtained by dissolving the alicyclic structure-containing polymer in the organic solvent for dissolution is 5 to 30% by weight, more preferably 10 to 20% by weight.

[0035] In the dissolving step, the method for dissolving the alicyclic structure-containing polymer in the organic solvent for dissolution is not particularly limited, but may be a method in which the alicyclic structure-containing polymer is added to the organic solvent for dissolution and then mixed.

[0036] <Radical generator addition process> The radical generator adding step in the production method of the present invention is a step of obtaining a solution (b) by adding a radical generator to the solution (a) obtained in the above-mentioned dissolving step.

[0037] The radical generator is not particularly limited as long as it is a compound that generates radicals by heating, but from the viewpoint of handling, it is preferable that the 10-hour half-life temperature is 80° C. or higher, and more preferably 120° C. or higher. Examples of such radical generators include dialkyl peroxides such as dicumyl peroxide, t-butylcumyl peroxide, 2,5-bis(t-butylperoxy)2,5-dimethylhexane, 2,5-bis(t-butylperoxy)2,5-dimethylhexyne-3, di-t-butyl peroxide, isopropylcumyl-t-butyl peroxide, and bis(α-t-butylperoxyisopropyl)benzene; 1,1-bis(t-butylperoxy)cyclohexane, 1,1-bis(t-butylperoxy)3,3,5-trimethylcyclohexane, 1,1-bis(t-butylperoxy)cyclododecane, n-butyl-4,4-bis(t-butylperoxy)valerate, and ethyl-3,3-bis(t-butylperoxy). ) butyrate, 3,3,6,6,9,9-hexamethyl-1,2,4,5-tetraoxycyclononane and other peroxyketals; bis(t-butylperoxy)isophthalate, t-butylperoxybenzoate, t-butylperoxyacetate and other peroxyesters; t-butyl hydroperoxide, t-hexyl hydroperoxide, cumin hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, diisopropylbenzene hydroperoxide, p-menthane hydroperoxide and other hydroperoxides; 2,3-dimethyl-2,3-diphenylbutane and other bibenzyl compounds; 3,3,5,7,7-pentamethyl-1,2,4-trioxepane and the like. These may be used alone or in combination of two or more. Among these, dialkyl peroxides are preferred, and dicumyl peroxide is more preferred.

[0038] The amount of the radical generator used is preferably 0.1 to 10 parts by weight, more preferably 0.5 to 7 parts by weight, and further preferably 1 to 6 parts by weight, based on 100 parts by weight of the alicyclic structure-containing polymer in the solution (a). By setting the amount of the radical generator used within the above range, the crosslinking reaction can be sufficiently advanced in the crosslinking step described below, and there is little risk of the radical generator remaining after the crosslinking reaction is completed, so that the progression of unexpected side reactions can be more appropriately suppressed.

[0039] In the radical generator addition step, it is preferable to further add a crosslinking agent to the solution (a) in addition to the radical generator. By adding the crosslinking agent, the crosslinked structure of the particles of the alicyclic structure-containing crosslinked polymer obtained after crosslinking can be made denser, and thus the strength can be further increased.

[0040] Examples of the crosslinking agent include bifunctional crosslinking agents such as divinylbenzene, divinyldiphenyl, divinylnaphthalene, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, N,N-divinylaniline, divinyl ether, diallyl phthalate, allyl (meth)acrylate, and pentaerythritol di(meth)acrylate; and trifunctional or higher crosslinking agents such as triallyl isocyanate, trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, dipentaerythritol poly(meth)acrylate, and ethoxylated versions thereof. These may be used alone or in combination of two or more. Among these, trifunctional crosslinking agents are preferred, and triallyl isocyanate is more preferred.

[0041] The amount of the crosslinking agent used is preferably 0.1 to 10 parts by weight, more preferably 0.5 to 8 parts by weight, and even more preferably 0.65 to 5 parts by weight, based on 100 parts by weight of the alicyclic structure-containing polymer in solution (a). By setting the amount of the crosslinking agent used within the above range, the effect of improving the strength of the particles of the alicyclic structure-containing crosslinked polymer obtained after crosslinking can be further enhanced.

[0042] In the radical generator addition step, the method of adding the radical generator and the crosslinking agent used as needed to the solution (a) obtained in the dissolving step described above is not particularly limited, but may be a method of adding the radical generator and the crosslinking agent used as needed to the solution (a) and mixing them.

[0043] <Emulsification process> The emulsification step in the production method of the present invention is a step of mixing an aqueous medium containing a dispersant with the solution (b) obtained in the above-mentioned radical generator addition step, and emulsifying the mixture to obtain an emulsion (c).

[0044] The dispersant is not particularly limited, and both organic and inorganic dispersants can be used. Examples of organic dispersants include water-soluble polymers such as polyvinyl alcohol, methyl cellulose, and gelatin; surfactants such as anionic surfactants, cationic surfactants, amphoteric surfactants, and nonionic surfactants; and the like. Examples of inorganic dispersants include metal oxides such as aluminum oxide and titanium oxide; sulfates such as barium sulfate and calcium sulfate; carbonates such as barium carbonate, calcium carbonate, and magnesium carbonate; phosphates such as calcium phosphate, magnesium phosphate, and aluminum phosphate; metal hydroxides such as aluminum hydroxide, magnesium hydroxide, and ferric hydroxide; inorganic particles such as silica, titanium dioxide, and aluminum oxide; silicone, and metal soap. The dispersant may be used alone or in combination of two or more. Among these, organic dispersants are preferred, and surfactants are more preferred from the viewpoint that the particle size of the particles of the alicyclic structure-containing crosslinked polymer after crosslinking can be made smaller.

[0045] Examples of the anionic surfactant include sodium fatty acid, potassium fatty acid, sodium alkylbenzene sulfonate, sodium alkyl sulfate, sodium alkyl ether sulfate, sodium alpha olefin sulfonate, and sodium alkyl sulfonate. Examples of the cationic surfactant include alkyltrimethylammonium salts and dialkyldimethylammonium salts. Examples of amphoteric surfactants include sodium alkylamino fatty acid, alkyl betaine, and alkyl amine oxide. Examples of nonionic surfactants include sucrose fatty acid esters, sorbitan fatty acid esters, polyoxyethylene sorbitan fatty acid esters, polyoxyethylene alkyl esters, fatty acid alkanolamides, polyoxyethylene alkyl ethers, polyoxyethylene alkylphenyl ethers, polyoxypropylene alkyl ethers, and polyoxypropylene fatty acid esters.

[0046] Among these surfactants, anionic surfactants are preferred, potassium fatty acid and sodium alkylbenzenesulfonate are more preferred, and potassium oleate and sodium dodecylbenzenesulfonate are even more preferred. The surfactants may be used alone or in combination of two or more.

[0047] As the aqueous medium, water may be used alone, but it may also be used in combination with an organic solvent that is soluble in water.

[0048] The aqueous medium containing a dispersant used in the emulsification step can be prepared by dissolving or dispersing the dispersant in the aqueous medium. The content of the dispersant in the aqueous medium containing the dispersant is not particularly limited, but is preferably 0.5 to 10% by weight, more preferably 1 to 8% by weight. By setting the content of the dispersant within the above range, the stability of the resulting emulsion (c) can be improved when the solution (b) prepared in the radical generator addition step is emulsified in the aqueous medium containing the dispersant.

[0049] In the emulsification step, when the aqueous medium containing a dispersant is mixed with the solution (b) prepared in the radical generator addition step, the proportions of these are not particularly limited, but the amount of the aqueous medium containing a dispersant used relative to 100 parts by weight of the solution (b) is preferably 200 to 600 parts by weight, and more preferably 300 to 500 parts by weight.

[0050] The aqueous medium containing a dispersant is mixed with the solution (b) prepared in the radical generator addition step, and emulsified to obtain the emulsion (c). The mixing method is not particularly limited, but is preferably a method using an emulsifier. Examples of the emulsifier include batch emulsifiers such as "Homogenizer" (manufactured by IKA), "Polytron" (manufactured by Kinematica), and "TK Auto Homo Mixer" (manufactured by Tokushu Kika Kogyo); continuous emulsifiers such as "TK Pipeline Homo Mixer" (manufactured by Tokushu Kika Kogyo), "Colloid Mill" (manufactured by Shinko Pantech), "Slasher" (manufactured by Nippon Coke and Engineering Co., Ltd.), "Trigonal Wet Fine Grinding Mill" (manufactured by Mitsui Miike Chemical Engineering Co., Ltd.), "Cavitron" (manufactured by Eurotech), "Milder" (manufactured by Pacific Machinery Co., Ltd.), and "Fine Flow Mill" (manufactured by Pacific Machinery Co., Ltd.).

[0051] In addition, in the manufacturing method of the present invention, it is preferable to use an organic solvent other than the organic solvent for dissolution used in the dissolving step as an organic solvent for addition, and to include such an organic solvent for addition in the emulsion (c) obtained in the emulsifying step. By including an organic solvent for addition other than the organic solvent for dissolution in the emulsion (c), the particle size of the alicyclic structure-containing polymer before crosslinking in the emulsion (c) can be suitably controlled, and thus the particle size can be made smaller than the particle size of the alicyclic structure-containing crosslinked polymer particles finally obtained after crosslinking.

[0052] Such an organic solvent for addition may be an organic solvent of a different type from the organic solvent for dissolution. From the viewpoint of more suitably controlling the particle size, the absolute value of the difference between the SP value of the organic solvent for dissolution and the SP value of the organic solvent for addition is preferably 0.2 to 14 MPa. 1 / 2 It is preferable to use an organic solvent having a viscosity of 0.2 to 5 MPa. 1 / 2 It is more preferable to use an organic solvent having a pressure of 1 to 3 MPa. 1 / 2 It is more preferable to use an organic solvent in which the absolute value of the difference between the SP value of the organic solvent for dissolution and the SP value of the organic solvent for addition is within the above range, thereby making it possible to make the particle size of the finally obtained particles of the alicyclic structure-containing crosslinked polymer after crosslinking smaller.

[0053] For the SP value, for example, a database value installed in the Hansen Solubility Parameter calculation software HSPiP (Version 5.3.03) can be used. Alternatively, for those not described in the publicly known literature, a value estimated using Aspen Plus, which is a simulation software for SP values, can be used as the SP value. In Aspen Plus, the SP value is calculated from the boiling point, critical point, critical pressure, evaporation enthalpy, and liquid molar volume estimated from the molecular structure. In addition, when a mixture of two or more types of organic solvents for dissolution and / or organic solvents for addition is used, the SP value of each organic solvent multiplied by the volume ratio and then added together can be used as the SP value. For example, when a first organic solvent and a second organic solvent are mixed, the SP value of the mixed solvent can be calculated according to the following formula. SP Mix =(SP 1 ×V 1 )+(SP 2 ×V 2 ) (In the above formula, SP Mix is the SP value of the mixed solvent, SP 1 is the SP value of the first organic solvent, SP 2 is the SP value of the second organic solvent, V 1 is the volume ratio of the first organic solvent, V 2 is the volume fraction of the first organic solvent, V 1 +V 2 =1.)

[0054] For example, cyclohexane (SP value: 16.8 MPa) is used as an organic solvent for dissolution. 1 / 2 When using toluene (SP value: 18.2 MPa), the organic solvent to be added should be toluene. 1 / 2 ), methyl ethyl ketone (SP value: 19.0 MPa 1 / 2 ), ethyl acetate (SP value: 18.6 MPa 1 / 2 ), n-hexane (SP value: 14.9 MPa 1 / 2 ), Butyl acetate (SP value: 17.0MPa 1 / 2), etc. can be suitably used, and among these, toluene, methyl ethyl ketone, and ethyl acetate are preferred.

[0055] The method for incorporating the organic solvent for addition into the emulsion (c) is not particularly limited, but examples thereof include the following methods (α), (β), and (γ). Method (α) An organic solvent for addition is added to an aqueous medium containing a dispersant, and emulsified to prepare an emulsion (c-1) containing an organic solvent for addition. Next, the solution (b) prepared in the radical generator addition step is added to the emulsion (c-1) containing an organic solvent for addition, and emulsified to obtain an emulsion (c). Method (β) An organic solvent for addition is added to the solution (b) prepared in the radical generator addition step and mixed to prepare a solution (b-1) containing an organic solvent for addition. The solution (b-1) containing an organic solvent for addition is mixed with an aqueous medium containing a dispersant and emulsified to obtain an emulsion (c). ·(γ) method During the operation of mixing and emulsifying an aqueous medium containing a dispersant with the solution (b) prepared in the radical generator addition step, an organic solvent for addition is added and mixing and emulsification are continued to obtain an emulsion (c).

[0056] Among the above-mentioned methods (α), (β), and (γ), from the viewpoint of further enhancing the effect of including an organic solvent for addition, methods (α) and (γ) are preferred, and method (α) is more preferred.

[0057] The amount of the organic solvent for addition is preferably 1 to 300 parts by weight, more preferably 5 to 250 parts by weight, relative to 100 parts by weight of the organic solvent for dissolution. By setting the amount of the organic solvent for addition within the above range, the particle size of the particles of the alicyclic structure-containing crosslinked polymer finally obtained in the emulsion (c) after crosslinking can be made smaller. Even when the organic solvent for addition is contained, the amount of the dispersant used and the amount of the aqueous medium containing the dispersant used may be within the above range.

[0058] <Crosslinking process> In the crosslinking step in the production method of the present invention, the emulsion (c) is heated to a temperature T 1 [° C.] to crosslink the alicyclic structure-containing polymer in the aqueous medium, thereby obtaining a slurry containing particles of the alicyclic structure-containing crosslinked polymer. 1 is a temperature equal to or higher than the 10-hour half-life temperature of the radical generator.

[0059] According to the crosslinking step, the alicyclic structure-containing polymer is crosslinked by the action of the radical generator by heating at a temperature equal to or higher than the 10-hour half-life temperature of the radical generator, and thus particles of the alicyclic structure-containing crosslinked polymer can be formed. In particular, in the production method of the present invention, since the crosslinking is advanced in an aqueous medium, the alicyclic structure-containing crosslinked polymer can be obtained in the form of particles having a small particle size and a high degree of circularity.

[0060] Heating temperature T in the crosslinking process 1[°C] may be a temperature equal to or higher than the 10-hour half-life temperature of the radical generator, but from the viewpoint of more appropriately proceeding with the crosslinking reaction, it is preferably set to a temperature 10°C higher than the 10-hour half-life temperature of the radical generator and 200°C or lower, and more preferably set to a temperature 20°C higher than the 10-hour half-life temperature of the radical generator and 180°C or lower. The heating time in the crosslinking step is preferably 2 hours to 12 hours, more preferably 3 hours to 5 hours. Since the crosslinking reaction is proceeded in an aqueous medium in the crosslinking step, the temperature of the aqueous medium and the alicyclic structure-containing polymer is usually set to a heating temperature T 1 By setting the temperature at [°C], the crosslinking reaction is allowed to proceed.

[0061] In the crosslinking step, the heating may be performed in a manner that allows the crosslinking reaction to proceed in the aqueous medium, but it is preferable to perform the heating in a state where the evaporation of the aqueous medium is suppressed, for example, by performing the heating in a sealed container such as an ampoule or an autoclave in a sealed state. According to the production method of the present invention, the crosslinking reaction is allowed to proceed in the aqueous medium in this way, so that the particles of the crosslinked polymer containing an alicyclic structure that are finally obtained can have a small particle size and a high circularity. In addition, in the crosslinking step of the present invention, the crosslinking can be sufficiently allowed to proceed in a particulate state, so that the loss tangent (tan δ) at 200 ° C. and the loss tangent (tan δ) at 250 ° C. that are finally obtained can be suitably made to satisfy a predetermined relationship described later.

[0062] <Organic solvent removal process> In the process for removing the organic solvent in the present invention, the emulsion (c) or the slurry is heated to a temperature T 2 In the organic solvent removal step, the emulsion (c) or the slurry is heated at a heating temperature T 2 The temperature should be 40 to 95°C.

[0063] The organic solvent removal step is a step carried out before or after the above-mentioned crosslinking step, and is carried out by heating the emulsion (c) obtained in the emulsification step or the slurry containing the particles of the alicyclic structure-containing crosslinked polymer obtained in the crosslinking step at a heating temperature T 2 At least a part of the organic solvent (dissolving organic solvent, adding organic solvent) contained in the emulsion (c) or the slurry is removed by heating at 30° C. That is, in the organic solvent removal step, it is sufficient to remove at least a part of the organic solvent (dissolving organic solvent, adding organic solvent) contained in the emulsion (c) or the slurry, and it is not necessary to remove all of it, but it is preferable to remove preferably 80% by weight or more, more preferably 90% by weight or more, and particularly preferably substantially all of the organic solvent (dissolving organic solvent, adding organic solvent) contained in the emulsion (c) or the slurry (dissolving organic solvent, adding organic solvent).

[0064] The organic solvent removal step may be carried out either before or after the crosslinking step described above, but is preferably carried out before the crosslinking step from the viewpoint of increasing the circularity of the particles of the finally obtained alicyclic structure-containing crosslinked polymer. When the organic solvent removal step is carried out before the crosslinking step, the heating temperature T 1 and the heating temperature T 2 By T 1 >T 2 Alternatively, when the organic solvent removal step is carried out after the crosslinking step, it is preferable to set the relationship as follows: T 1 <T 2 In addition, the 10-hour half-life temperature of the radical generator is preferably the heating temperature T 2 When the temperature is in the range of 40 to 95°C, T 1 =T 2 In other words, in the production method of the present invention, "performing the organic solvent removal step before or after the crosslinking step" also includes "performing the organic solvent removal step simultaneously with the crosslinking step".

[0065] Heating temperature T in the organic solvent removal process 2 The temperature [°C] may be 40 to 95°C and may be appropriately selected depending on the type of organic solvent used, but is preferably 60 to 95°C, and more preferably 80 to 92°C. The heating time in the organic solvent removal step is preferably 1 to 5 hours, and more preferably 2 to 4 hours.

[0066] <Recovery process> The recovery step in the production method of the present invention is a step of recovering the alicyclic structure-containing crosslinked polymer particles from the slurry containing the alicyclic structure-containing crosslinked polymer particles that has been subjected to the above-mentioned crosslinking step and organic solvent removal step.

[0067] In the recovery step, the method for recovering the particles of the alicyclic structure-containing crosslinked polymer is not particularly limited, but may be, for example, a method such as dehydration and filtration. The dehydration and filtration methods may be any of various known methods, and are not particularly limited. For example, centrifugal filtration, vacuum filtration, pressure filtration, etc. may be used.

[0068] In addition, in the recovery step, the particles of the alicyclic structure-containing crosslinked polymer may be recovered after a washing operation. The washing operation may include a method of centrifuging the slurry containing the particles of the alicyclic structure-containing crosslinked polymer, removing the supernatant solution, and then adding washing water such as ion-exchanged water to reslurry the slurry. The washing operation may be repeated several times.

[0069] In the recovery step, the recovered particles of the alicyclic structure-containing crosslinked polymer may be dried as necessary. The drying temperature is preferably 20 to 160° C., more preferably 30 to 140° C., and further preferably 40 to 120° C. By setting the drying temperature within the above range, the recovered particles of the alicyclic structure-containing crosslinked polymer can be sufficiently dried while appropriately suppressing fusion of the particles.

[0070] <Particles of crosslinked polymer containing alicyclic structure> The particles of the alicyclic structure-containing crosslinked polymer of the present invention are particles made of a crosslinked product of the alicyclic structure-containing polymer, and have a volume average particle size of 0.5 to 100 μm and an average circularity of 0.90 to 1.00.

[0071] The particles of the alicyclic structure-containing crosslinked polymer of the present invention can be obtained, for example, by the production method of the present invention described above, but are not particularly limited to those obtained by the production method of the present invention described above.

[0072] The particles of the alicyclic structure-containing crosslinked polymer of the present invention have a volume average particle size of 0.5 to 100 μm, preferably 0.5 to 20 μm, and more preferably 0.5 to 2.0 μm. The volume average particle size of the particles of the alicyclic structure-containing crosslinked polymer can be measured by a laser diffraction method using a laser diffraction particle size distribution measuring device.

[0073] The particles of the alicyclic structure-containing crosslinked polymer of the present invention have an average circularity of 0.90 to 1.00, preferably 0.92 to 1.00, and more preferably 0.94 to 1.00. The average circularity can be determined by determining the circularity calculated by the following formula for 1,000 or more particles and calculating the average value. Circularity = (perimeter of a circle equal to the projected area of ​​the particle) / (perimeter of the projected image of the particle)

[0074] Furthermore, it is preferable that the particles of the alicyclic structure-containing crosslinked polymer of the present invention satisfy the following formula (1) when the loss tangent (tan δ) at 200°C is defined as "tan δ(200)" and the loss tangent (tan δ) at 250°C is defined as "tan δ(250)" in a temperature dependency curve of the loss tangent (tan δ) obtained by performing dynamic viscoelasticity measurement at a frequency of 1 Hz. {tanδ(200)-tanδ(250)} / 50>0 (1)

[0075] Since the particles of the alicyclic structure-containing crosslinked polymer of the present invention are crosslinked alicyclic structure-containing polymers, even when heated to 200° C. or higher, the loss tangent (tan δ) measured by dynamic viscoelasticity measurement does not increase with heating, and the loss tangent (tan δ) at 200° C. is slightly decreased when compared with the loss tangent (tan δ) at 250° C. On the other hand, when no crosslinking is performed, the loss tangent (tan δ) increases rapidly with the increase in temperature due to heating when heated to 200° C. or higher, and the value of the loss tangent (tan δ) at 250° C. becomes large, and “{tan δ(200)-tan δ(250)} / 50” in the above formula (1) shows a large negative value.

[0076] The particles of the crosslinked polymer containing an alicyclic structure of the present invention have a volume average particle size and an average circularity within the above range, and have a small particle size and a high circularity. Also, since the particles are crosslinked products of the crosslinked polymer containing an alicyclic structure, they have a high glass transition temperature, excellent heat resistance, and excellent shape stability. Therefore, the particles of the crosslinked polymer containing an alicyclic structure of the present invention can be suitably used as a light diffusing agent, a powder coating material, a toner material, an ink, a spacer for liquid crystal displays, a filler, an antiblocking agent, a lubricant component, a powder for forming a three-dimensional object, and the like.

[0077] The particles of the alicyclic structure-containing crosslinked polymer of the present invention may be produced by, for example, the following production method other than the production method of the present invention described above. That is, A dissolving step of dissolving the alicyclic structure-containing polymer in an organic solvent for dissolution to obtain a solution (a); a radical generator addition step of obtaining a solution (b) by adding a radical generator to the solution (a) obtained in the dissolving step; an emulsification step of mixing an aqueous medium containing a dispersant with the solution (b) and emulsifying the mixture to obtain an emulsion (c); The emulsion (c) is heated to a temperature T 2 an organic solvent removal step of removing the organic solvent in the emulsion (c) by heating at [° C.]; a recovery step of recovering particles of the alicyclic structure-containing polymer from the emulsion (c) from which the organic solvent has been removed; In the recovery step, the recovered particles of the alicyclic structure-containing polymer are heated to a heating temperature T 1 and a crosslinking step of crosslinking the alicyclic structure-containing polymer by heating at a temperature of [° C.] to obtain particles of the alicyclic structure-containing crosslinked polymer, The heating temperature T 1 is a temperature equal to or higher than the 10-hour half-life temperature of the radical generator, and the heating temperature T 2 The temperature may be 40 to 95° C. by a method for producing particles of an alicyclic structure-containing crosslinked polymer.

[0078] That is, in the above-mentioned production method, the particulate alicyclic structure-containing polymer is recovered from the emulsion (c), and the recovered alicyclic structure-containing polymer particles are heated at a temperature equal to or higher than the 10-hour half-life temperature of the radical generator to advance the crosslinking reaction, thereby obtaining alicyclic structure-containing crosslinked polymer particles. EXAMPLES

[0079] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples. In addition, "parts" are by weight unless otherwise specified. Various measurements were carried out according to the following methods.

[0080] <Volume average particle size (laser diffraction method)> The volume average particle diameter of the particles in the emulsion and the particles of the cyclic olefin resin crosslinked product was measured using a laser diffraction particle size distribution measuring device (product name "SALD2200", manufactured by Shimadzu Corporation). Note that, in Comparative Example 1, the particles of the cyclic olefin resin crosslinked product were aggregated and solidified, so that the volume average particle diameter of the particles of the cyclic olefin resin crosslinked product could not be measured.

[0081] <Particle size (optical microscope)> The particles of the cyclic olefin resin crosslinked product were observed with an optical microscope, and the particle diameters of 100 particles were measured to determine the particle diameter distribution (particle diameter range). Note that, in Comparative Example 1, the particles of the cyclic olefin resin crosslinked product were aggregated and solidified, and the particle diameters of each particle constituting the aggregated and solidified cyclic olefin resin crosslinked product were observed and measured with an optical microscope to determine the particle diameter distribution (particle diameter range).

[0082] <Average circularity> 10 ml of ion-exchanged water was placed in a container, 0.2 g of a surfactant aqueous solution (manufactured by Fujifilm Corporation, product name: Drywell) was added as a dispersant, and 0.2 g of particles of a crosslinked cyclic olefin resin was added, followed by dispersion treatment for 3 minutes at 60 W using an ultrasonic disperser. The particle concentration of the crosslinked cyclic olefin resin at the time of measurement was adjusted to 3,000 to 10,000 particles / μL, and 1,000 to 10,000 particles of the crosslinked cyclic olefin resin were measured using a flow-type particle image analyzer (manufactured by Sysmex Corporation, product name: FPIA-2100). The average circularity was calculated from the measured value. The circularity is expressed by the following formula, and the average circularity is the average value thereof. Circularity = (perimeter of a circle equal to the projected area of ​​the particle) / (perimeter of the projected image of the particle)

[0083] <Viscoelasticity> Dynamic viscoelasticity measurements were performed on the particles of the cross-linked cyclic olefin resin (an agglomerated solid of the cross-linked cyclic olefin resin particles for Comparative Example 1, and solid cyclic olefin resin for Comparative Example 2) to obtain temperature dependence curves of the storage modulus (G') and loss tangent (tan δ), and the values ​​of the loss tangent at 200°C (tan δ(200)), the loss tangent at 250°C (tan δ(250)), and {tan δ(200)-tan δ(250)} / 50 were determined. The dynamic viscoelasticity measurement was performed using a rotating plate rheometer (TA Instruments, ARES-G2) with a crosshatch plate under the following conditions: Test pieces were prepared by pouring 0.2 g of toner into a cylindrical molding machine with a diameter of 8 mm, applying pressure of 1.0 MPa for 30 seconds, and molding into a cylindrical body with a thickness of 3 mm and a diameter of 8 mm. (Conditions for dynamic viscoelasticity measurement) Measurement frequency: 1Hz Sample set: A test piece (3 mm thick) was clamped between 8 mm diameter plates with a load of 20 g, the temperature was raised to 160°C, the test piece was fused to the jig, and then the temperature was returned to 120°C and the temperature increase started. Heating rate: 5℃ / min Measurement temperature range: 120~250℃

[0084] <Glass transition temperature> For the particles of the crosslinked cyclic olefin resin (for Comparative Example 1, the aggregated solidified particles of the crosslinked cyclic olefin resin), DSC curves were obtained by high-speed differential scanning calorimetry during temperature rise and fall. For the differential scanning calorimetry (DSC) using the high-speed differential scanning calorimeter, silicone oil was applied to the chip sensor using the tip of a brush and spread as a pretreatment of the sample. By applying silicone oil to the chip sensor, the particles of the crosslinked cyclic olefin resin after measurement do not fuse to the chip sensor, so that the particles of the crosslinked cyclic olefin resin after measurement can be removed, and the same chip sensor can be reused. As a result, the baseline becomes stable between samples, and data with good reproducibility can be obtained. About 10 particles of the crosslinked cyclic olefin resin (for Comparative Example 1, an amount equivalent to 10 particles) were placed on the chip sensor to which silicone oil was applied, and the particles of the crosslinked cyclic olefin resin were measured using an ultra-high-speed DSC device (Mettler Toledo, Flash DSC) under a nitrogen gas flow under the following temperature conditions (1) to (5). (1) Hold at 0°C for 0.1 seconds. (2) The temperature is increased from 0°C to 150°C at 1000 K / s. (3) Hold at 150°C for 60 seconds. (4) The temperature is decreased from 150°C to 0°C at -1000K / sec. (5) Hold at 0°C for 1 second. The glass transition temperature of the particles of the cyclic olefin resin crosslinked product was determined as the temperature at the intersection of a straight line extending from the low-temperature side baseline to the high-temperature side in the DSC curve during heating in high-speed differential scanning calorimetry and a tangent drawn at the stepwise change part of the glass transition or the point where the slope of the curve of the endothermic peak due to enthalpy relaxation is maximum.

[0085] <Production Example 1> (Preparation of Cyclic Olefin Resin) A tank-type reactor equipped with a stirrer was fully purged with nitrogen, and 20 parts of ethylidenetetracyclododecene, 200 parts of cyclohexane, 2.0 parts of 1-hexene, 15 parts of a 15% by weight solution of triethylaluminum in toluene, and 5.0 parts of triethylamine were added to the reactor, and the temperature was kept at 20°C. While stirring, 80 parts of ethylidenetetracyclododecene and 9.0 parts of a 20% by weight solution of titanium tetrachloride in toluene were continuously added over 60 minutes. After reacting for 1 hour, the reaction was stopped by adding 5.0 parts of ethyl alcohol and 2.0 parts of water. The reaction solution was heated to 40°C to hydrolyze the catalyst, and then 3 parts of calcium sulfate and 60 parts of cyclohexane were added to remove excess water. The precipitate containing the deposited metal was removed by filtration, and 371 parts of a transparent polymer solution containing an ethylidenetetracyclododecene ring-opening polymer was obtained. This procedure was repeated, and 15 parts of Ni-diatomaceous earth catalyst (N113, manufactured by Nikki Chemical Co., Ltd.) was added to 750 parts of the polymer solution, which was then placed in a pressure-resistant reactor and hydrogen was introduced to a pressure of 50 kg / cm. 2 The hydrogenation reaction was carried out for 3 hours at a temperature of 200° C. After the reaction was completed, 700 parts of cyclohexane was added for dilution, and the catalyst was removed by filtration to obtain 1,350 parts of a polymer solution containing a hydrogenated ring-opened polymer.

[0086] 800 parts of the polymer solution containing the ring-opening polymer hydrogenation product obtained above was passed through a column packed with 4.5 parts of activated alumina (Mizusawa Chemical Industries, Ltd., Neobead D) with an inner diameter of 10 cm and a length of 100 cm so that the residence time was 100 seconds, and circulated for 24 hours. 550 parts of this solution was poured into 1500 parts of isopropanol with stirring to coagulate the ring-opening polymer hydrogenation product. The coagulated ring-opening polymer hydrogenation product was collected by filtration, washed twice with 300 parts of isopropanol, and then dried in a rotary vacuum dryer at 5 torr and 120°C for 48 hours to obtain a cyclic olefin resin.

[0087] <Example 1> The cyclic olefin resin obtained in Production Example 1 was dissolved in cyclohexane so that the concentration of the cyclic olefin resin was 20% by weight, thereby obtaining a solution (a) (a cyclohexane solution containing 20% ​​by weight of the cyclic olefin resin) (dissolving step). Next, 2.6 parts of dicumyl peroxide (manufactured by Nippon Oil & Fats Corporation, product name "Percumyl D", 10-hour half-life temperature: 116.4°C) as a radical generator and 2.0 parts of triallyl isocyanurate (manufactured by Tokyo Chemical Industry Co., Ltd.) as a crosslinking agent were added to 258 parts of the obtained solution (a) to obtain a solution (b) (radical generator addition step).

[0088] Next, 73.1 parts of a 16% by weight aqueous solution of potassium oleate and 9 parts of sodium dodecylbenzenesulfonate (manufactured by Kao Corporation, product name "Neopelex G-65") were mixed with 1000 parts of ion-exchanged water to obtain a dispersant aqueous solution, and 506 parts of toluene and 10 parts of methyl ethyl ketone were added to the obtained dispersant aqueous solution, and emulsified with an emulsifier (manufactured by Eurotech, product name "Cavitron") to obtain an emulsion of organic solvent for addition. Then, the total amount (1598.1 parts) of the emulsion of organic solvent for addition prepared above was dispersed with the emulsifier, and the total amount (262.6 parts) of the solution (b) obtained above was added to the emulsion of organic solvent for addition during dispersion, and emulsified by mixing to obtain an emulsion (c) (emulsification step).

[0089] Next, N 2While injecting gas, the temperature was raised from 50°C to 92°C at a heating rate of 0.2°C / min, and then the organic solvent was removed by heating at 92°C for 180 minutes, followed by water cooling to obtain emulsion (c) after the organic solvent was removed (organic solvent removal step). Note that, in emulsion (c) after the organic solvent removal, almost all of the organic solvents (cyclohexane, toluene, methyl ethyl ketone) used were removed (the same applies to Example 2 and Comparative Example 1 described below). Next, emulsion (c) after the organic solvent removal was placed in an autoclave, and N 2 After purging the gas, the autoclave was kept sealed and heated at 140°C for 180 minutes to crosslink the cyclic olefin resin, thereby obtaining a slurry containing particles of the cyclic olefin resin crosslinked product (crosslinking process).

[0090] Next, the obtained slurry containing the cyclic olefin resin crosslinked product was centrifuged to remove the supernatant, and ion-exchanged water was added to reslurry, and the washing operation was repeated four times, followed by drying to obtain particles of the cyclic olefin resin crosslinked product (recovery step). Then, the particles in the emulsion (c) obtained by the emulsification step were measured for volume average particle size (laser diffraction method) according to the above-mentioned method, and the particles of the obtained cyclic olefin resin crosslinked product were measured for volume average particle size (laser diffraction method), particle size (optical microscope), average circularity, viscoelasticity, and glass transition temperature according to the above-mentioned method. The results are shown in Table 1.

[0091] <Example 2> Except for changing the amount of triallyl isocyanurate to 1.0 part, and using 466 parts of toluene and 50 parts of ethyl acetate instead of 506 parts of toluene and 10 parts of methyl ethyl ketone, particles of a cyclic olefin resin crosslinked product were obtained in the same manner as in Example 1, and each measurement was performed in the same manner.

[0092] <Comparative Example 1> The amount of solution (a) (20% by weight cyclohexane solution of cyclic olefin resin) used was changed to 516 parts, the amount of dicumyl peroxide used to 2.3 parts, and the amount of triallyl isocyanurate used to 1.0 part, and 506 parts of toluene and 10 parts of methyl ethyl ketone were replaced with 264 parts of toluene and 32 parts of ethyl acetate, respectively, and the same procedure as in Example 1 was repeated to obtain emulsion (c) after removal of the organic solvent. 2 The particles of the cyclic olefin resin crosslinked product were obtained by heating in an open system under the conditions of 120°C and 3.0 hours in a gas atmosphere using a dryer (oven), and each measurement was performed in the same manner. In Comparative Example 1, the particles of the cyclic olefin resin crosslinked product were coagulated and solidified, and the form of the coagulated solidified product was obtained. In Comparative Example 1, the emulsion (c) was heated with the start of heating using the dryer (oven), and the water in the emulsion (c) was removed with the heating of the emulsion (c), and the water was completely removed at a temperature sufficiently lower than 116.4°C, which is the 10-hour half-life temperature of dicumyl peroxide as a radical generator. Therefore, in Comparative Example 1, it can be said that the crosslinking reaction of the cyclic olefin resin proceeded in a state where the water was completely removed (i.e., in a state where no aqueous medium was present).

[0093] <Comparative Example 2> In Comparative Example 2, the cyclic olefin resin obtained in Production Example 1 was used as it was, and each measurement was carried out in the same manner.

[0094] [Table 1]

[0095] As shown in Table 1, the particles of the alicyclic structure-containing crosslinked polymer (cyclic olefin resin crosslinked product) obtained by the production method of the present invention had a small particle size and a high degree of circularity (Examples 1 and 2). On the other hand, when crosslinking is performed in a state where water is completely removed by heating in an open system using a dryer (oven) (i.e., in a state where no aqueous medium is present), the particles of the alicyclic structure-containing crosslinked polymer aggregate and solidify, making it impossible to obtain a particulate alicyclic structure-containing crosslinked polymer (cyclic olefin resin crosslinked product). In addition, the loss tangent (tan δ) at 200°C and the loss tangent (tan δ) at 250°C measured by viscoelasticity measurement did not satisfy the above formula (1) (Comparative Example 1).

Claims

1. A dissolving step of dissolving the alicyclic structure-containing polymer in an organic solvent for dissolution to obtain a solution (a); a radical generator addition step of obtaining a solution (b) by adding a radical generator to the solution (a) obtained in the dissolving step; an emulsification step of mixing an aqueous medium containing a dispersant with the solution (b) and emulsifying the mixture to obtain an emulsion (c); The emulsion (c) is heated to a temperature T 1 a crosslinking step of crosslinking the alicyclic structure-containing polymer in the aqueous medium by heating at [° C.] to obtain a slurry containing particles of the alicyclic structure-containing crosslinked polymer; Before or after the crosslinking step, the emulsion (c) or the slurry is heated to a heating temperature T 2 an organic solvent removal step of removing the organic solvent in the emulsion (c) or the slurry by heating at [° C.]; A recovery step of recovering particles of the alicyclic structure-containing crosslinked polymer from the slurry, The heating temperature T 1 is a temperature equal to or higher than the 10-hour half-life temperature of the radical generator, and the heating temperature T 2 The present invention relates to a method for producing particles of a crosslinked polymer having an alicyclic structure, the temperature being 40 to 95° C.

2. 2. The method for producing particles of an alicyclic structure-containing crosslinked polymer according to claim 1, wherein the emulsion (c) further contains an organic solvent for addition other than the organic solvent for dissolution used in the dissolving step.

3. The absolute value of the difference between the SP value of the organic solvent for dissolution and the SP value of the organic solvent for addition is 0.2 to 14 MPa. 1/2 The method for producing particles of the alicyclic structure-containing crosslinked polymer according to claim 2, wherein

4. Particles of an alicyclic structure-containing crosslinked polymer having a volume average particle size of 0.5 to 100 μm and an average circularity of 0.90 to 1.00, Particles of an alicyclic structure-containing crosslinked polymer that satisfies the following formula (1), when the loss tangent (tan δ) at 200° C. is defined as "tan δ(200)" and the loss tangent (tan δ) at 250° C. is defined as "tan δ(250)" in a temperature dependency curve of loss tangent (tan δ) obtained by performing dynamic viscoelasticity measurement at a frequency of 1 Hz: {tanδ(200)-tanδ(250)} / 50>0 (1)

Citation Information

Patent Citations

  • Modified cyclic olefin copolymer

    JP1993271356A

  • Crosslinkable norbornene resin composition and molding made therefrom

    JP1994248164A

  • Resin particle

    JP2000336151A

  • Method for producing cyclic olefin-based resin particle

    JP2010059360A